An International Law and National Resilience Perspective for Internationalizing Religious Moderation as Indonesia’s Soft Diplomacy Legal Instrument in ASEAN - Hartono, Achdwiyanto Yudi; Hamdi, Ahmad Zainul (Khazanah Hukum, 2026)
Indonesia, as the largest country in Southeast Asia, plays a strategic role in shaping regional stability and political dynamics within ASEAN. At the same time, regional developments, particularly the rise of religious radicalism and transnational terrorism, have significant implications for Indonesia’s national resilience. In this context, this article examines how Indonesia can strengthen its regional leadership through the internationalization of religious moderation as a legal and diplomatic instrument within ASEAN. The study analyzes the legal foundations of religious moderation policy in Indonesia, including constitutional principles, statutory regulations, and Presidential Regulation No. 58 of 2023, which institutionalizes the promotion of religious moderation as part of national policy. Using a normative qualitative legal approach, this article explores the intersection of law, religion, and diplomacy in promoting regional stability. The findings show that the internationalization of religious moderation can function as a form of soft diplomacy and normative leadership, enabling Indonesia to translate domestic legal norms into regional normative practices. This approach is consistent with ASEAN’s principles of consensus and non-interference, while also contributing to broader efforts to counter violent extremism and strengthen human security in the region. Furthermore, the study argues that religious moderation can be positioned as part of Indonesia’s non-military defense strategy, supporting the development of regional legal norms that promote peaceful coexistence and social resilience. Ultimately, the research highlights Indonesia’s opportunity to institutionalize religious moderation within ASEAN’s legal and diplomatic framework as part of its constitutional mandate to contribute to international peace and stability.